2013
DOI: 10.5194/bg-10-5639-2013
|View full text |Cite
|
Sign up to set email alerts
|

Saturated CO<sub>2</sub> inhibits microbial processes in CO<sub>2</sub>-vented deep-sea sediments

Abstract: Abstract. This study focused on biogeochemical processes and microbial activity in sediments of a natural deep-sea CO2 seepage area (Yonaguni Knoll IV hydrothermal system, Japan). The aim was to assess the influence of the geochemical conditions occurring in highly acidic and CO2 saturated sediments on sulfate reduction (SR) and anaerobic methane oxidation (AOM). Porewater chemistry was investigated from retrieved sediment cores and in situ by microsensor profiling. The sites sampled around a sediment-hosted h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, it cannot be excluded that diffuse flow of liquid or supercritical CO 2 leads to pronounced CaCO 3 dissolution in the sediment and that these processes affect the geochemistry of the near‐bottom layer of both systems (lowermost 10 m of the water column) which have not been investigated geochemically in this study. Very high A T values measured in pore waters of the upper sediment close to active sites in YK [ de Beer et al ., ; Neumann , ] support this assumption, however, further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it cannot be excluded that diffuse flow of liquid or supercritical CO 2 leads to pronounced CaCO 3 dissolution in the sediment and that these processes affect the geochemistry of the near‐bottom layer of both systems (lowermost 10 m of the water column) which have not been investigated geochemically in this study. Very high A T values measured in pore waters of the upper sediment close to active sites in YK [ de Beer et al ., ; Neumann , ] support this assumption, however, further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…The seafloor at YK is mainly covered with muddy sediments of terrigenous origin [ Suzuki et al ., ] and is strongly affected by carbonate and silicate weathering at the vent sites [ de Beer et al ., ; Häckel et al ., ].…”
Section: Study Sites and Sampling Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stream CO2-97 is representative of a fluid mixture coming from a gas-fired plant using the pre-combustion 8 capture process and contains 3% of impurities with about 1% of N 2 and less than 2% of CH 4 (Table 1) (Metz et al, 2005). Submarine venting of natural liquid CO 2 has been recently observed and it has been shown that CO 2 -saturated seawater should inhibit sulfate reduction and anaerobic methane oxidation (AOM) in deep-sea sediments (de Beer et al, 2013).…”
Section: Co 2 Stream Composition (Co2-96 Co2-97 Co2-100)mentioning
confidence: 99%
“…Submarine venting of natural liquid CO 2 has been previously observed only at a few submarine volcanoes (Lupton et al, 2006;de Beer et al, 2013). The study in laboratory of the dynamics of the gas hydrates in sedimentary medium (namely formation, accumulation and destabilization processes) is still at its beginnings.…”
Section: Introductionmentioning
confidence: 99%